Effect of Pretreatments and Drying Methods on Quality of Ber During Storage - Gupta, Neeraj; Kaul, Raj Kumari (Annals of Arid Zone, 2016)
The effects of methods of drying and storage on viability of ber were studied at Sher-e-Kashmir University of Agricultural Sciences and Technology, Jammu. Different pretreatments were subjected to ber fruits before dehydration, viz. blanching in boiling water for six minutes to inactivate enzyme activity followed by one per cent KMS dip for five minutes, sulphur fumigation for two hours @ 3.5 g kg-1 fruit and then dying by sun and oven methods. Dried ber were stored at room temperature and analysed after 2, 4 and 6 months to study changes in physico-chemical characteristics. During bimonthly studies an increasing trend was observed in rehydration ratio, browning and iron content, where as ascorbic acid, phosphorus and calcium content decreased. After six months of storage sulphur treated fruits (8.00, 7.00 and 6.80) followed by KMS treated fruit (7.80, 6.80 and 6.50) in color, texture and flavour were found to be the best in oven-dried samples as compared to sun-dried samples. Key words: Ber, drying, storage, quality.